Implementasi Kebijakan dalam Pemanfaatan Fitur E-Kelurahan pada Aplikasi Sangu Palu di Kelurahan Taipa, Kecamatan Palu Utara, Kota Palu - Imelda Safitri; Asrifai Asrifai; Syamsul Bahri (Fakultas Teknik Universitas Cenderawasih, 2026)
This study aims to examine the implementation of policies regarding the use of the e-Kelurahan feature in the Sangu Palu application in Taipa Village. The study employs George C. Edward III’s policy implementation theory, which consists of four dimensions: communication, resources, disposition, and bureaucratic structure. A qualitative descriptive approach was used, with data collected through observation, in-depth interviews, documentation, and literature review involving nine informants. The findings indicate that the implementation of the e-Kelurahan policy has not yet run optimally. The main obstacle lies in the communication aspect, particularly the lack of direct public socialization regarding the use of the application, resulting in low public understanding and limited utilization of digital services. In addition, training for village officials has not been conducted continuously, as it was only provided during the initial implementation stage. Therefore, periodic retraining is needed to improve technical competence and evaluate service performance. Although the aspects of disposition and bureaucratic structure have generally functioned well, they have not been sufficient to optimize digital service utilization. These findings are consistent with the Electronic-Based Government System (SPBE) evaluation results, which place Palu City in the “sufficient” category, indicating the need for further improvement in digital service implementation.